Survey and Analysis of Water Quality in Phou Chom Voy Provincial Protected Area of Bolikhamxay Province: https://doi.org/10.69692/SUJMRD0802323 - Keoinpaeng, Sopha; Deevanxay, Phengxay; Chounlamany, Vanseng; Phouthavong, Vanpaseuth; Kongmany, Santi (Souphanouvong University Journal Multidisciplinary Research and Development, 2022)
Investigation of water quality in Phou Chom Voy Provincial Protected Area is an important sustainable forest management planning and conservation. Phou Chom Voy is located in the Khamkerd and Xaychamphone district, Bolikhamxay Province. It is rich in natural resources and biodiversity, and origin of many streams. This study aimed to investigate the water quality in the streams flowing through the Phou Chom Voy area as an initial indicator of water quality change. Water samples were collected from 13 sites (Heung Tai, Heung Noua, Jing Nga, Pakeo, Heung Neua, Tin Tok, Huay Lurk, Houay Ha, Nam Pan, Nam Khai, Houay Yeung, Houay Ja, Houay Jalai and Nam Tong) and water sampling was carried out 2 times a year from November 2017 to February 2020. The results found that pH 5.3 - 9.3, EC 10.0 - 84.9 µs/cm, DO 5.0 - 8.6 mg/L, PO43- ND - 0.06 mg/L, NO3 - ND - 2.18 mg/L, Cu ND - 0.03 mg/L, Zn ND - 0.81 mg/L, As ND - 0.007 mg/L, Cd ND - 0.007 mg/L, Cr ND - 0.028 mg/L, Pb ND - 0.004 mg/L, Hg ND - 0.002 mg/L, all concentrations of each paprametere found in this study were below the maximum allowable values of the Laos’s national environmental standards on groundwater.